Assistance Model for Slow Learners in Inclusive Early Childhood Education: A Case Study Based on Field Practice in Buleleng, Bali - Ni Putu Sinta Dewi (Universitas Pendidikan Ganesha, 2026)
The inclusion of slow learners in early childhood education requires a specific assistance model that aligns with local characteristics, especially in regions with strong cultural values like Buleleng. This study aimed to explore and analyze the assistance model for slow learners in inclusive Early Childhood Education (ECE) in Buleleng Regency. This qualitative study employed a case study design, involving classroom teachers and Special Assistant Teachers (GPK) as research subjects. Data were gathered through field observations, in-depth interviews, and documentation at several inclusive ECE centers, using observation guidelines, interview protocols, and documentation sheets as research instruments. Data were analyzed using an interactive analysis model, including data reduction, data display, and conclusion drawing.The results indicated that an effective assistance model integrates the Individualized Education Program (IEP), curriculum modification based on local wisdom (Tri Hita Karana), and intensive collaboration between classroom teachers and Special Assistant Teachers (GPK). While challenges such as limited experts and low parental literacy persist, the strength of local community support (Pawongan) serves as a vital pillar for the sustainability of inclusive programs. Overall, a collaborative and culturally responsive assistance model can enhance the effectiveness of inclusive learning for slow learners. The implications of this study emphasize the importance of strengthening professional collaboration, optimizing curriculum adaptation, and increasing community involvement to support sustainable inclusive education practices.